RISK ASSESSMENT FOR HEALTH OF POPULATION IN AN INDUSTRIAL CITY FROM ATMOSPHERIC EMISSIONS OF PLANT OF CONSTRUCTION PRODUCTS - Суржиков, Дмитрий Вячеславович; Кислицына, Вера Викторовна; Корсакова, Татьяна Георгиевна (Medicine in Kuzbass, 2017)
Subject – atmospheric emissions of LLC «Plant of construction products». Objective. To determine the ecological risk to public health from emissions of LLC «Plant of construction products» in the atmosphere of Novokuznetsk. Methods. Calculation of indexes of carcinogenic and non-carcinogenic hazards of the emissions of LLC «Plant of construction products»; comparison of total risks of chronic intoxication and carcinogenic risk with acceptable levels at exposure points. Main results. Dioxide of nitrogen, nitrogen oxide and kerosene have the highest index of non-carcinogenic hazard; the maximum index of carcinogenic danger is detected in soot. The average concentrations of non-carcinogenic and carcinogenic substances by the exposure points expressed in multiples of MPC do not exceed the norm. The total risk of developing non-carcinogenic effects is maximal in Novobaydaevsky microdistrict. Carcinogenic risk is the greatest among the residents of microdistricts of Novobaydaevsky and Aviator prosp. Conclusions. Emissions of the plant of construction products do not have a chronic inhalation effect on the population of Novokuznetsk. The rate of excess of acceptable risk with the total value of the carcinogenic risk of inhalation effects is within the normal range.